Evaluation of nominal operating cell temperature (NOCT) of glazed photovoltaic thermal module - Vat Sun (Case Studies in Thermal Engineering, 2021)
Nominal operating cell temperature (NOCT) was commonly used to evaluate photovoltaic (PV) module temperature and this term is provided by the manufacturer but in case of photovoltaic thermal module, the NOCT was not fixed and varied with the circulating fluid mass flow rate and its temperature. In this study, a novel approach on NOCT evaluation of glazed photovoltaic thermal (PVTg) module for combined heat and power generation was presented by modifying the method of solar collector testing for water heating. The thermal characteristics in terms of optical and heat loss performances and finally the NOCT at various water flow rates and inlet temperatures could be evaluated. Experimental tests were performed with a PVTg module under Chiang Mai climate, and it could be founded that the calculated module temperature, the outlet hot water temperature and the generated electrical power agreed well with the experimental results. Monthly performance of this module was also evaluated and compared with unglazed PVT and conventional PV modules each having the same solar photovoltaic cell type. The average generated electrical outputs were 28.07, 31.89, and 30.38 kWh/month, respectively, while the glazed and the unglazed PVT modules could generate average thermal energy of 119.19 and 101.40 kWh/month, respectively.